Recurrent oral ulcerations associated with recurrent herpes labialis – two distinct entities? - Katz J, Chaushu G, Peretz B (Blackwell Synergy, 2001)
We investigated the prevalence of recurrent aphthous ulcerations (RAU) and recurrent herpes labialis (RHL) in a young adult population. The study group consisted of 20 689 soldiers (aged 18–21 years, mean 19.8º1 years).